Entre imigrantes e nativos digitais : a percepção docente sobre as novas tecnologias da informação e comunicação (NTIC) e o ensino da educação física - Indalécio, Anderson Bençal (Universidade Federal de São Carlos, 2015)
This study aimed to understand facts arising from educational processes applied to the teaching of Physical Education at the level of Basic Education, established by agents of different generations and mediated by resources of the new technology. The systematic analysis of the phenomenon permeated the understanding of factors related to the level of perception about the technology object of teachers classified as Immigrants and Digital Natives in the first instance; for later verification of the concerted relationship between the concreteness of the perceptible level expressed by the teacher and the appropriation of technological tools in teaching and learning processes in which they act. Based in a referential qualitative research, the methodology used for the range of explanations about this theme connected the instruments of data collection: structured questionnaire; interviews by guidelines class observations and filmings. The application of research understood two moments, as follows: a diagnostic exploration of the above dimension in the context of the totality of individuals who constitute the population of research, formed by Physical Education teachers effectives in a municipal school system of a municipal district of Northwest Paulista, and therefore, extensive analysis in details of vision and respective practice of teachers of both generational categories, and distinct levels of perception about the New Technologies of Information and Communication, the pedagogical approach mediated by technological resources applied to Physical Education at school. In this context was verified that those involved in the processes of appropriation of technological resources and applied together the learners are influenced to a greater extent by the level of perception maintained by the individual with the technological object, therefore, not justified necessarily the generational dimension of the teacher. This way, the adequation of significant educational proposals with the use of the New Technologies of Information and Communication remits to the perception and respective critically appropriation of technology in personal and professional daily use. In the end, about the interaction processes objectified in constructing of new knowledge, the potential didactic and conceptual gaps resulting from pedagogical actions mediated by technological resources in educational practices observed tend to be minimized by reflective communicative actions, directed to the dialogue between the educator agents, educating and technological object.
Between immigrants and digital natives: the perception teacher about the new technologies of information and communication and the teaching of physical education
Keywords: Gerações; Tecnologia; Processos educativos; Agir comunicativo; Dialogicidade; Generations; Technology; Educational processes; Communicative action; Dialogism; CIENCIAS HUMANAS::EDUCACAO